2022
DOI: 10.15575/likuid.v2i1.14915
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review Potential Development of Halal Industry in Indonesia

Abstract: This study aims to explain the potential of the Halal Industry in Indonesia. This research also identifies opportunities and challenges in its development. The method used in this research is descriptive-qualitative method with a phenomenological approach. The data obtained were analyzed using qualitative analysis through data reduction, categorization and verification. This study found that Indonesia has the potential to develop the Halal Industry in various sectors, especially halal food, halal tourism, hala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…This involves providing reliable halal certification, as well as educating the public about the importance of choosing halal products in accordance with their religious principles. With cooperation between the government and the community, the halal product industry in Indonesia has enormous potential to continue to grow and develop (Izzudin & Adinugraha, 2021).…”
Section: Strategies To Increase Halal Products In Improving the Compe...mentioning
confidence: 99%
“…This involves providing reliable halal certification, as well as educating the public about the importance of choosing halal products in accordance with their religious principles. With cooperation between the government and the community, the halal product industry in Indonesia has enormous potential to continue to grow and develop (Izzudin & Adinugraha, 2021).…”
Section: Strategies To Increase Halal Products In Improving the Compe...mentioning
confidence: 99%
“…Indonesia, as a country with the largest Muslim majority population, certainly has great potential in the halal food industry. This is also revealed by Izzudin & Adinugraha (2021) that Indonesia has the potential to develop the halal industry in various sectors, especially halal food, halal tourism, halal fashion, halal pharmaceuticals, and halal cosmetics. The Indonesian government has established the Halal Product Guarantee Agency (BPJPH) to promote and regulate the halal industry, because the government aims to make Indonesia the world's halal center and the pioneer of halal industry globalization (Maulana et al, 2024).…”
Section: Introductionmentioning
confidence: 98%
“…Despite these efforts, the development of Indonesia's halal industry still faces challenges such as low awareness of halal, low competitiveness of local products, and problems in implementing the Halal Product Guarantee Regulation (Izzudin & Adinugraha, 2021). Febriati et al (2024) added that the halal food industry in Indonesia faces challenges in managing the supply chain, especially in ensuring the availability of raw materials and maintaining the integrity of food products throughout the supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…A study by (Izzuddin & Adinugraha, 2022) found that Indonesia could develop the Halal Industry in various sectors, especially halal food, tourism, halal fashion, pharmaceuticals, and cosmetics. The development of the Halal Industry also has the potential to increase national economic growth.…”
Section: Introductionmentioning
confidence: 99%